First report on two cases of pleomorphic dermal sarcoma successfully treated with immune checkpoint inhibitors. (2nd December 2019) - Klein, Sebastian; Persa, Oana-Diana; Mauch, Cornelia; Noh, Ka-Won; Pappesch, Roberto; Wagener-Ryczek, Svenja; Buettner, Reinhard; Quaas, Alexander; Helbig, Doris
ABSTRACT: Pleomorphic dermal sarcoma (PDS) is one of the most common sarcoma of the skin. Currently, limited treatment options exist for advanced stages of the disease. While immune checkpoint inhibitors (CPIs) have revolutionized cancer treatment options–their efficacy in PDS has not been explored yet. Here, we present two advanced PDS cases that showed response to anti-PD-1 therapy. Patient A had a locally metastasized PDS and reached a complete remission of the disease after eight cycles of Pembrolizumab. Patient B developed an inoperable relapse of PDS with a complete remission of the disease 4 months after treatment with Pembrolizumab in combination with radiotherapy. To our knowledge, this is the first report of two individuals with advanced PDS that successfully underwent anti-PD1 treatment. By comparing the immune micromilieu to a previously published cohort, we show that the two cases are representative for PDS tumors – potentially making these results more generalizable.